APPLICATION OF CRIMINAL SANCTIONS AGAINST CHILDREN AS A PERPETRATORS OF ABUSE THAT CAUSE DEATH FROM THE JUVENILE CRIMINAL JUSTICE SYSTEM PERSPECTIVE - Novita Lestari; Tofik Yanuar Chandra; Sanrawan Paparang (Transpublika Publisher, 2022)
The main objective of this study is to describe the application of criminal sanctions against children who commit acts of abuse that result in death, as well as the legal protection from the viewpoint of the Juvenile Criminal Justice System. This study employs a normative juridical legal research research methodology; the technique used in this legal research is statutory, case-based, and conceptual approach. The study's study found that the legal regulation of children who commit violent crimes under the Criminal Code does not reflect an authentic understanding of what constitutes violence. Only in article 89 of the Criminal Code does it indicate that what constitutes committing violence causes individuals to faint or become helpless (weak). Along with Article 89 of the Criminal Code, Article 170 is one of the articles included in Book II on Crime's Chapter V headed